Does job embeddedness mediate the effects of coworker and family support on creative performance? An empirical study in the hotel industry. Issue 2 (2nd April 2016) - Karatepe, Osman M.
ABSTRACT: Drawing from conservation of resources and job embeddedness theories, this study examines whether job embeddedness mediates the effects of coworker and family support on creative performance. Data gathered from frontline hotel employees and their supervisors in Cameroon were used to test these relationships. The results from structural equation modeling suggest that the presence of coworker and family support fosters employees' job embeddedness. Employees with such resources display creative performance. In short, there is strong support for the fully mediated model that coworker and family support enhance creative performance via job embeddedness. Implications of the results are discussed and future research directions are offered.